Peaty soil improvement by using cationic reagent grout and electrokinetic method - Moayedi, Hossein; Mosallanezhad, Mansour; Nazir, Ramli; Kazemian, Sina; Kim Huat, Bujang (Springer, 2014)
Peat is known as soft soil with low shear strength and high compressibility. Electrokinetic injection technique is being used by applying a direct electrical potential across the soil specimens to improve physicochemical characteristics of the peat. Such applications cause electrochemical effects on the soil, leading to changes in the soil’s chemical, physical, and mechanical properties. This paper presents the results of the undrained shear strength, pH, water content across the electrokinetic box after injecting the cationic grouts. Four cationic grouts namely; calcium chloride, calcium oxide, Aluminum hydroxide, and sodium silicates were selected as grout. The microstructures of the stabilized peats were investigated by scanning electron microscopy and energy dispersive X-ray spectrometer analysis. The result showed that the cationic stabilizer injected by the electrokinetic technique could significantly increase the peat soil’s shear strength. Furthermore, the result showed that the effect of calcium oxide was the highest on the shear strength of peat due to its physico-chemical properties. The shear strength, pH and moisture content of peats across the electrokinetic box also altered depending on the used electrolytes and time.